Coastal Erosion Hazard Map at Pantai Perpat and Pantai Punggur, Batu Pahat, Johor - AFIF ALTAF BIN MOHD EZUAN'IZAM; Muhammad Affendi Alias; Nur Farisha Mohd Fakarruddin; Suhaila Sahat (Multidisciplinary Applied Research and Innovation, 2025)
Coastal erosion is a major problem in Malaysia, impacting the country’s coastline and providing a variety of environmental, economic, and social difficulties. Several causes contribute to Malaysian coastal erosion including changes in sea rate and monsoons that occur in Malaysia. This will lead to increase erosion and infrastructure damage, as well as other natural disasters such as floods and landside. This research investigates the coastal erosion hazard map at the Pantai Punggur and Pantai Perpat coastlines in Batu Pahat, Johor.The aim are to produce a diagram mapping the beach profile and beach hazards around the two beaches. Google Earth Pro software was used to obtain data and ArcGIS software analyse the study are for each parameter. Data was collected from a previous study, which provided essential information on geomorphology, shoreline change rate, coastal slope, relative sea level rate, and mean significant wave height. Findings reveal significant variability at different spatial scales, influenced by natural processes such as waves, currents, sea level, tectonics, and storms, as well as human activities like construction, coastal structures, sand mining, and dune destruction. The study highlights the need for proper coastal management plans, including beach filling and nourishment projects, to mitigate severe erosion threats and hazards.